Adverse event management in patients with relapsed and refractory multiple myeloma taking pomalidomide plus low‐dose dexamethasone: A pooled analysis. (14th June 2017) - Moreau, Philippe; Dimopoulos, Meletios A.; Richardson, Paul G.; Siegel, David S.; Cavo, Michele; Corradini, Paolo; Weisel, Katja; Delforge, Michel; O'Gorman, Peter; Song, Kevin; Chen, Christine; Bahlis, Nizar; et al.
Abstract: Objectives: Heavily pretreated patients with relapsed and refractory multiple myeloma are susceptible to treatment‐related adverse events (AEs). Managing AEs are important to ensure patients continue therapy long enough to receive the best clinical benefit. Data from the MM‐002, MM‐003, and MM‐010 trials were pooled to further characterize the safety profile of pomalidomide plus low‐dose dexamethasone and AE management. Methods: This analysis included 1088 patients who received ≥ 2 prior therapies, including lenalidomide and bortezomib, and progressed ≤ 60 days of last therapy. Patients received 28‐day cycles of pomalidomide 4 mg/day on days 1‐21 and low‐dose dexamethasone 40 mg (20 mg if aged > 75 years) weekly until disease progression or unacceptable toxicity. Thromboprophylaxis was required. Results: The most common grade 3/4 AEs were neutropenia (56.2%), anemia (32.3%), and thrombocytopenia (25.8%), which occurred within the first few cycles of treatment. Grade 3/4 infections occurred in 33.7% patients, of whom 13.9% had pneumonia, and 40.3% had neutropenia. Pomalidomide dose reductions or interruptions were reported in 24.2% and 66.0% of patients, respectively. AEs were managed by dose modifications and/or supportive care. Conclusions: Pomalidomide plus low‐dose dexamethasone showed an acceptable safety profile, and AEs were well managed according to study protocols and established guidelines.